The Impact of Urinary Catheterization on the Antibiotic Susceptibility of ESBL-Producing Enterobacterales: A Challenging Duo - Ionela-Larisa Miftode; Andrei Vâță; Radu-Ștefan Miftode; Tudorița Parângă; Mihaela Cătălina Luca; Carmen Manciuc; Amalia Stefana Țimpău; Viorel Radu; Manuel Florin Roșu; Lidia Oana Stămăteanu; Daniela Leca; Dana Teodora Anton-Păduraru; et al. (MDPI AG, 2024)
Introduction: Antimicrobial resistance (AMR) is currently a growing concern among healthcare providers, underscoring the importance of describing the regional susceptibility profile for common microorganisms that are associated with urinary tract infections (UTIs). This knowledge serves as the foundation for proper empirical therapeutic recommendations tailored to local susceptibility patterns. Results: We found a high prevalence of ESBL-producing strains (36.9%), with Escherichia coli and Klebsiella spp. being the most prevalent isolated bacteria. Among the catheterized patients, Klebsiella spp. emerged as the primary etiology, with a significant correlation between catheterization and Proteus spp. (p = 0.02) and Providencia stuartii (p < 0.0001). We observed significant correlations between urinary catheterization and older age (68.9 ± 13.7 years vs. 64.2 ± 18.1 years in non-catheterized patients, p = 0.026) and with the presence of an isolate with extensive drug resistance (p < 0.0001) or even pandrug resistance (p < 0.0001). Susceptibility rates significantly decreased for almost all the tested antibiotics during the study period. Notably, susceptibility was markedly lower among catheterized patients, with the most pronounced differences observed for carbapenems (59.6% versus 83.4%, p < 0.0001) and aminoglycosides (37.1% versus 46.9%, p = 0.0001). Materials and Methods: We conducted a retrospective study analyzing the susceptibility profiles of 724 extended-spectrum beta-lactamases (ESBL)-producing Enterobacterales isolated from urine cultures. Our focus was on highlighting susceptibility profiles among isolates associated with urinary catheterization and assessing the shifts in the susceptibility rates over time. Conclusions: The constant rise in AMR rates among Enterobacterales presents significant challenges in treating severe infections, particularly among urinary catheterized patients. This trend leaves clinicians with limited or no effective treatment options. Consequently, the development and implementation of personalized treatment protocols are imperative to ensure efficient empirical therapies.